2016
DOI: 10.1080/02640414.2016.1194527
|View full text |Cite
|
Sign up to set email alerts
|

Differences in strength and speed demands between 4v4 and 8v8 small-sided football games

Abstract: The aims of this study were (i) to characterise the acceleration demands of two different formats of small-sided game (SSG), i.e., 4v4 + goalkeepers (4v4 + GK) and 8v8 + goalkeepers (8v8 + GK); (ii) to analyse the correlation between performance in power-based tests and acceleration-based physical loading during the two different SSG formats and (iii) to analyse the neuromuscular-induced fatigue. Eighteen adult male footballers participated in the study (20.7 ± 1.0 years, 178 ± 5 cm and 71.4 ± 2.1 kg). Baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 35 publications
10
69
0
9
Order By: Relevance
“…Por otro lado, además de las respuestas de los jugadores ante distintos tipos de JR, también se ha analizado la fatiga, expresada como la pérdida de rendimiento físico posterior a realizar la tarea que inducen este tipo de formatos de entrenamiento (33). Estos autores observaron que los JR en los que participan un menor número de jugadores y menos EII por jugador provocaban una pérdida de rendimiento en la capacidad de sprint de 5 y de 15 m que no provocaba un JR con más jugadores y más EII.…”
Section: Introductionunclassified
“…Por otro lado, además de las respuestas de los jugadores ante distintos tipos de JR, también se ha analizado la fatiga, expresada como la pérdida de rendimiento físico posterior a realizar la tarea que inducen este tipo de formatos de entrenamiento (33). Estos autores observaron que los JR en los que participan un menor número de jugadores y menos EII por jugador provocaban una pérdida de rendimiento en la capacidad de sprint de 5 y de 15 m que no provocaba un JR con más jugadores y más EII.…”
Section: Introductionunclassified
“…lower running distance with more accelerations/decelerations in sized-reduced games), game-based trials with smaller pitch areas and number of players have been reported to induce greater play intensity and number of short-term activities including spurts, changes of directions and stoppages (Malone et al, 2016;Rebelo et al, 2016a). In contrast, FM have been shown to produce greater player displacements with minimal accelerations and decelerations (David Casamichana et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous reports (Malone et al, 2016;Rebelo, Silva, Rago, Barreira, & Krustrup, 2016a) our hypothesis was that LSG, compared to SSG, would elicit more accurate movement patterns to those during a competitive, friendly match.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations